2015
DOI: 10.1016/j.ijsu.2015.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Fifty top-cited classic papers in orthopedic elbow surgery: A bibliometric analysis

Abstract: Identification of the most cited papers in elbow surgery shows an insight into the historical development of elbow surgery and provides the foundation for further investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
108
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(120 citation statements)
references
References 38 publications
9
108
0
3
Order By: Relevance
“…The peak period is closer to the present time than it was found in other citation analysis studies [12,13] . This may indicate that visceral surgery is a young and dynamic field, and clinicians rely on latest research as suggested by Shuaib et al [5] analyzing highly cited papers in the cardiovascular area.…”
Section: Discussionsupporting
confidence: 73%
“…The peak period is closer to the present time than it was found in other citation analysis studies [12,13] . This may indicate that visceral surgery is a young and dynamic field, and clinicians rely on latest research as suggested by Shuaib et al [5] analyzing highly cited papers in the cardiovascular area.…”
Section: Discussionsupporting
confidence: 73%
“…Overall, we found a strong widespread presence in cartilage-related research. While the United States had the greatest contribution in the overwhelming majority of other bibliometric analyses in orthopedic subspecialties, 11,17,18,20,28 this study found that only 17 of the top 50 articles (34%) had corresponding authors from the United States, with Sweden, Canada, the United Kingdom, and other countries contributing articles to the most-cited list. Among all authors, the most frequently cited were M. Brittberg (Sweden), L. Hangody (Hungary), and L. Peterson (Sweden).…”
Section: Discussionmentioning
confidence: 68%
“…3). 11,12,17,19 This sizeable number of randomized controlled trials and prospective cohort studies reflects the increasing emphasis on evidence-based practice across all medical disciplines in recent years since the concept was introduced and popularized in the 1990s. 31 Indeed, this study found that there was a statistically significant increase in the quality of evidence with transition into the modern era after the 1990s and 2000s (P = 0.003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, we may have inadvertently omitted important publications by search criteria chosen. Lastly, the method of using journal citations as a measure is potentially skewed due to authors’ self-citations or due to a “snowball effect” which can result when some authors cite certain articles simply because they have been cited before but not necessarily due to their relevance to a publication [18,19]. …”
Section: Discussionmentioning
confidence: 99%